UAV-borne radar RF transceiver design and testing - Wang, Zhixiang (2016)
For the last two years, staff from Temasek Laboratory@NTU and some EEE students have been working on a multi-rotor based FMCW synthetic aperture radar system. Some SAR images are obtained. The paper of this project is attached as Appendix A after this report. In the old system, many up-convert stages are used to obtain a 600MHz bandwidth chirp signal centered at 15GHz. To reduce the use of RF components, a PLL plus VCO can be a solution of the signal source. In this report, a Ku band FMCW (Frequency Modulated – Continuous Wave) radar transceiver is implemented for target detection. The radar prototype is configured based on ADF4159 evaluation board and some RF components. The ADF4159 evaluation board is a product of Analog Devices which is a fractional N PLL frequency synthesizer with 13GHz RF bandwidth. Some basic analysis was done on this board to generate a suitable chirp signal centered at 12.3GHz with 600MHz bandwidth. The transmitting signal is able to provide a range resolution of 0.25m. Calculations and testing were done to verify the ability of detecting target of the FMCW radar system.